One-pot synthesis of Ag@Fe3O4/reduced graphene oxide composite with excellent electromagnetic absorption properties. Issue 3 (April 2015) - Liu, Gongzong; Jiang, Wei; Wang, Yanping; Zhong, Suting; Sun, Danping; Liu, Jie; Li, Fengsheng
Abstract: A ternary composite of Ag@Fe3 O4 /reduced graphene oxide (RGO) was synthesized by a facile one-pot solvothermal route and the electromagnetic absorption properties of the composite were investigated. The structure and morphology of the composite were characterized by X-ray diffraction, Raman spectroscopy, transmission electron microscopy and scanning electron microscopy. Interestingly, plenty of Ag/Fe3 O4 core/shell particles are well-distributed on the surface of graphene nanosheets. The magnetic hysteresis measurement reveals the ferromagnetic behavior of the composite at room temperature. The electromagnetic absorption properties show that the maximum reflection loss of Ag@Fe3 O4 /RGO is up to −40.05 dB at 11.9 GHz and the absorption bandwidth with the reflection loss below −10 dB is 3.1 GHz (from 9.4 to 12.5 GHz) with a thickness of 2 mm. The absorption bandwidth with the reflection loss below −10 dB is up to 13.5 GHz with a thickness in the range of 1.5–5.0 mm. The remarkable electromagnetic absorption properties of Ag@Fe3 O4 /RGO composite can be attributed to the multiple absorbing mechanisms. It is believed that such a composite could serve as an attractive candidate for electromagnetic absorber.